Pemberdayaan Kelompok Dasa Wisma dalam Pengembangan Pertanian pada Lahan Sempit di Desa Puo Raya, Kecamatan Tandun, Kabupaten Rokan Hulu - Hambali Hambali; Uci Siska Cahyati; Tasria Yaningsih; Sari Rezky Sinambela; Debi Pratiwi; Dhiya Nazhi Ifa; Yuda Prastio; Sherly Arsendi Arfa Sormin; Suci Lapena Anggun Salita; Risma Elviani; Jhon Roy Mulya Sinaga (LP2M Universitas Muhammadiyah Enrekang, 2022)
Empowerment aims to develop a potential that is owned by each individual or society. Dasa Wisma Empowerment is a PKK work program consisting of 10 – 20 houses in 1 RT, community service activities are carried out in Puo Raya Village from July to August 2022. This program aims to increase the knowledge and skills of Dasa Wisma group members about cultivation organic herbs and vegetables in a narrow area. These activities include the manufacture of organic fertilizers, training on how to plant and care for plants. After the training, it is hoped that the Dasa Wisma group will have skills in making organic fertilizers, planting and caring for organic herbs and vegetables. The selection of this program is due to the large number of narrow lands that can still be used to improve the family's economy through agricultural development. The results show that the Dasa Wisma group has been able to carry out the cultivation of organic herbs and vegetables well even though the land is narrow, as evidenced by well-developed plants and vegetables. Plants and vegetables resulting from agricultural development on this narrow land can support the family's economy because the yields are quite large.